SOCIAL IDENTITY AND ITS IMPACTS ON YOZO OBA’S ALIENATION IN “NO LONGER HUMAN” - Prasetya, Alvionita Zyahwalian; Thohiriyah, Thohiriyah (BASIS (Bahasa dan Sastra Inggris), 2024)
This research is conducted to understand social identity development and its impacts on alienation experienced by Yozo Oba, the main character in Osamu Dazai’s No Longer Human (1958). This study applies the Social Identity Theory (SIT) by Trepte & Loy (2017) and Fromm’s theory of alienation (in Nadhiroh, 2015) to analyze how Yozo’s experiences influence his social identity development and how it affects his actions throughout his life. This research uses a qualitative descriptive approach and a close-reading method to collect and analyze the data. The primary data is the English translation of the novel by Donald Keene (1958), and secondary data is collected from journals, articles, and books related to SIT and the theory of alienation. The analysis of Yozo Oba using the principles of Social Categorization, Social Identity, and Self-Esteem from SIT, and the concept of alienation from oneself, alienation from others, and alienation from society shows that Yozo Oba developed a dissatisfying social identity which affected his experience and behaviors, and led him to feel alienation from himself, others, and the society.